Mechanical assist devices for acute cardiogenic shock - Ni hlci, Tamara (Cochrane Database Syst Rev, 2018)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: The primary objective of this review is to assess whether mechanical assist devices improve survival in individuals with acute cardiogenic shock.